Eksistensi Lembaga Mahkamah Agung Sebagai Pelaksana Peradilan Yang Independen Dalam Rekrutmen Hakim - Arman, Zuhdi; Raju Moh Hazmi; Yon Efri; Sari (Universitas Muhammadiyah Bima, 2022)
The main issue discussed in this study is the extent to which the Supreme Court's power is autonomous in recruiting judges with the status of public officials for judicial organizations under its jurisdiction. Since legislation is the main source of information, this study takes a normative legal approach. The results of the study indicate that the current legal framework is not yet fully capable of regulating, implementing and ensuring the judicial system accurately, as well as the nature and status of judges as public officials. The current system and structure of the recruitment of judges continues to show a lack of transparency and uncertainty regarding the legal rules governing the recruitment of judges with the status of public officials. Existing norms maintain weak legitimacy, as they are not regulated by the Constitution, which establishes an independent judiciary responsible for upholding law and justice. Therefore, in the future it is necessary to adopt new rules and regulations governing the system and procedure for recruiting judges in accordance with the specificity of the position of judges as public officials to ensure the performance and accountability of judicial duties.